2014
DOI: 10.1309/ajcpbx74qxcpxikk
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Correlation Between p16INK4a Staining, Specific Subtype of Human Papillomavirus, and Progression of LSIL/CIN1 Lesions

Abstract: There is a significant relationship between p16(INK4a) immunostaining and follow-up (P = .002). p16(INK4a)-negative specimens or positivity in the lower one-third of CIN1 lesions seldom progress to a CIN2-3 lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
1
13
1
Order By: Relevance
“…However, a recent study concluded that the hrHPV subtype is a poor predictor of the behavior of a LSIL/CIN1 lesion. 29 Another controversial issue is that the biopsy procedure might alter the natural evolution of lesions favoring spontaneous resolution, particularly of small lesions. However, previous studies using either cytology or biopsy have shown no effect of the biopsy on the short-term evolution of LSIL/ CIN1 lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study concluded that the hrHPV subtype is a poor predictor of the behavior of a LSIL/CIN1 lesion. 29 Another controversial issue is that the biopsy procedure might alter the natural evolution of lesions favoring spontaneous resolution, particularly of small lesions. However, previous studies using either cytology or biopsy have shown no effect of the biopsy on the short-term evolution of LSIL/ CIN1 lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies have tried to assess whether p16 can stratify patient risk of CIN2/3 by scoring of the prevalent CIN1 biopsy [3][4][5][6][7][8] in studies in which case numbers ranged from 64 to 171, raising questions about the statistical power of the observed results. Furthermore, there is some variability in author interpretations of p16, although they generally agree that staining that fails to extend through the lower one third of the epithelium is negative.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Other studies have looked at CIN1 p16 and/or Ki-67 positivity as a harbinger of subsequent CIN2/3+ diagnosis with promising results but limited data sets. [3][4][5][6][7][8] Importantly, such studies are ultimately querying the prognostic rather than the diagnostic value of these markers. To accurately assess prognosis, one must work from a data set populated by cases with adjudicated diagnoses to best approximate a histologic "criterion standard," by minimizing diagnostic variability, which can be considerable.…”
mentioning
confidence: 99%
“…19 Additionally, in HIV-1 positive specimens there is a potential reason for caution when interpreting the immunohistochemical staining of p16 in cervical lesions. 20 Razmpoosh et al 21 conducted a study matching the immunohistochemical staining with DNA-HPV data by polymerase chain reaction, and found that p16 expression with a diffuse staining pattern was associated with high-risk HPV. They suggested that cases with a p16/HPV ratio within the high-risk range should not be considered to have clinical value, because the mere presence of high risk HPV is a poor predictor of CIN 1.…”
mentioning
confidence: 99%